Development of Tools for Identifying the Emergency Operation Parameters of Ukrainian IPS for the Digital Emergency Prevention and Protection of Automatics at Dniester PSPP - Stognii, B.S.; Kyrylenko, O.V.; Pavlovsky, V.V.; Steliuk, A.O.; Lukianenko, L.M. (Science and Innovation, 2024)
The basic phases of innovation project on the development of means enabling to identify the emergency operation parameters at the Dniester pumped storage power plant (PSPP) have been considered. The verification results of AVR models at Dniester PSPP have been shown. The basic information and data on the designed means for automating the steady-state and dynamic stability calculations have been provided. The structure diagram of the emergency system prototype of Dniester PSPP has been presented.